Association of a Variant of CNR1 Gene Encoding Cannabinoid Receptor 1 With Gilles de la Tourette Syndrome - Szejko, Natalia; Fichna, Jakub Piotr; Safranow, Krzysztof; Dziuba, Tomasz; Żekanowski, Cezary; Janik, Piotr (Frontiers in Genetics, 2020)
Background Gilles de la Tourette syndrome (GTS) is a neuropsychiatric disorder of unknown etiology, although a major role of genetic factors has been established. Cannabis-based medicines may alleviate GTS-associated tics and variants of CNR1 gene encoding central cannabinoid receptor (CB1) are believed to be a risk factor for the development of some neurodevelopmental diseases. Our aim was to test the association of selected CNR1 gene variants with GTS. Material and methods The cohort of GTS cases comprised 262 unrelated patients aged 3-53 years (mean age: 18.3 ± 9.1 years; 204 males (77.9%), 126 (48.1%) adults defined as ≥18 years). As a control group we enrolled 279 unrelated, ethnically and gender matched individuals with no diagnosed mental, neurological or general disorder, aged 13-54 years (mean age: 22.5 ± 3.0 years; 200 males, (74.1%). Both study and control groups were selected from Polish population, which is ethnically homogenous subgroup of Caucasian population. Four single nucleotide polymorphisms (SNPs) in CNR1 were selected: rs2023239, rs2180619, rs806379, rs1049353 based on minor allele frequency in general population >15%. These variants were genotyped using a real-time quantitative polymerase chain reaction system (TaqMan SNP genotyping assay). Results We found significant association of GTS clinical phenotype with rs2023239 variant. Minor allele C and CT+CC genotypes were found significantly more often in GTS patients compared to controls (17.4 vs 11.1%, p=0.003 and 32.8 vs 20.4%, p=0.001, respectively), and the difference remained significant after correction for multiple testing. C allele of rs2023239 polymorphism of the CNR1 gene was associated with the occurrence of tics. There were no statistically significant associations for rs806379, rs1049353 or rs2180619 variants. Conclusion Our findings suggest that C allele of rs2023239 polymorphism of the CNR1 gene is a risk factor of GTS in Polish population. The variant can be potentially associated with abnormal endocannabinoid transmission, which is suspected to be one of the causes of GTS.